Direct Cinema Tradition in Contemporary Argentinian Documentary (Palimpsesto, 2017)
This paper studies the aesthetic and political implications on the recovery of Direct Cinema forms in contemporary Argentine documentary. First, the essay proposes an historical and theoretical examination of the most important Direct Cinema characters. Then, the article analyses two documentary films as El etnógrafo (Ulises Rosell, 2012) and La toma (Sandra Gugliotta, 2013) in order to review some of the tensions that observational documentary mode raised in the representations of marginalized or divergent social actors, as well as their capacity for social criticism when hegemonic mass media hold the rule of non-fictional audiovisual representations.
Keywords: Documentary; Direct Cinema; Argentina; Contemporary; Tradition.